2010
DOI: 10.1111/j.1466-7657.2010.00826.x
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the Uganda nurses' and midwives' association for a motivated workforce

Abstract: The nurses lack continuing professional development, mentoring and networking opportunities. Tangible support for communication, nurse education and research is needed and will stimulate the development of nursing in Uganda. Most nurses do not have the means to pay for training, research or travel to attend professional meetings. Motivation to stay in nursing and quality of care can increase through investing in nursing, and this support can be channelled through associations such as the UNANM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…To gain a closer understanding of their views, I conducted a series of semi-structured interviews, asking which practices and factors could help to enhance their satisfaction with their nursing care work. The themes our discussions uncovered were very similar to the results of other studies conducted in both industrialized and low-income countries [126][127][128].…”
Section: Discussionsupporting
confidence: 74%
“…To gain a closer understanding of their views, I conducted a series of semi-structured interviews, asking which practices and factors could help to enhance their satisfaction with their nursing care work. The themes our discussions uncovered were very similar to the results of other studies conducted in both industrialized and low-income countries [126][127][128].…”
Section: Discussionsupporting
confidence: 74%
“…The results of the survey were provided to UANM with suggestions about improvements, new projects and communications to be offered by the organization. It was clear that the Ugandan nurse who participated in the survey development would take responsibility for the implementation of these suggestions (Zuyderduin et al. 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a needs assessment was conducted of Ugandan nurses to evaluate the effectiveness of the UANM. The results of the survey laid the foundation for boosting membership in the association and suggesting a variety of improvements for the organization to create a strategy for retaining nurses in Uganda (Zuyderduin et al. 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, nurses are capable of contributing to the design and implementation of research to improve health outcomes; however, particularly in low-and middle-income countries (LMICs), they require access to capacity building and training initiatives to build their research skills. In a recent Ugandan survey, 80% of nurses and midwives reported that they were interested in training opportunities to develop research skills (Zuyderduin, Obuni, & McQuide, 2010). The Institute of Medicine (2010) suggested that although nurses are well positioned to lead positive change and advance health, barriers such as the dearth of nurse researchers with doctoral-level training prevent nurses from effectively responding to rapidly changing health care settings and systems.…”
Section: Background To Research Programmentioning
confidence: 99%